Impact of social compliance on employee motivation: An empirical study - Alam M.N.; Alias R.B.; Hassan M. (Science and Engineering Research Support Society, 2023)
The primary purpose of this study is to observe the relationship between important social compliance variables (wages & benefits, discrimination, harassment & abuse, leave & holidays, welfare facilities) and employee motivation. The present study was conducted through positivism philosophy, and by employing Herzberg Two Factor Theory for framing the hypotheses. Furthermore, the study also employed a deductive approach, explanatory research design, and a quantitative methodology. In all, 500 samples were collected from Bangladesh ready-made garment industry through self-administrated scheduled questionnaire method. In addition, the used of Smart-PLS and SPSS was used in analysing and developing the model of the present study. As such, the outcome of the analysis revealed that all five hypotheses were supported. Based on this, it is hoped that this finding will assist the policymakers, government of Bangladesh, factory owners, managers, as well as other stakeholders to formulate the succeeding policy and practice. Finally, it is recommended for further research to employ other social compliance variables, which are not included in this study. 2019 SERSC.